A robust nonlinear PI-type controller for the DC–DC buck–boost power converter. (October 2022) - Martinez-Lopez, Mizraim; Moreno-Valenzuela, Javier; He, Wei
Abstract: In this study, a novel Lyapunov function-based robust nonlinear proportional–integral (PI)-type controller for regulating the output voltage of the direct current to direct current (DC–DC) inverting buck–boost power converter operating in continuous conduction mode (CCM) is presented. The control scheme guarantees global asymptotic stability of the closed-loop system even in case of parameter uncertainty. The analysis of the closed-loop trajectories is carried out using Lyapunov method and LaSalle's invariance principle. Robustness to additive disturbances is shown and simple gain tuning guidelines are given. Real-time experiments support the theoretical results. Experimental tests are presented where the proposed PI-type control design is compared with other PI-type schemes found in the literature. The proposed scheme presents very good consistent performance under line and load disturbance. Highlights: A robust nonlinear PI-type controller for the DC-DC buck–boost is proposed. A rigorous stability analysis of the closed-loop system is presented. The given solution is proven to be robust to additive disturbances. A simple tuning guideline results from the design. Real-time experiments verify the performance of the proposed controller.